Cognitive clinico-radiological paradox in early stages of multiple sclerosis - Uher, Tomas; Krasensky, Jan; Sobisek, Lukas; Blahova Dusankova, Jana; Seidl, Zdenek; Kubala Havrdova, Eva; Sormani, Maria Pia; Horakova, Dana; Kalincik, Tomas; Vaneckova, Manuela (Annals of clinical and translational neurology, 2018)
OBJECTIVE: To investigate whether the strength of the association between magnetic resonance imaging (MRI) metrics and cognitive outcomes differs between various multiple sclerosis subpopulations. METHODS: A total of 1052 patients were included in this large cross-sectional study. Brain MRI (T1 and T2 lesion volume and brain parenchymal fraction) and neuropsychological assessment (Brief International Cognitive Assessment for Multiple Sclerosis and Paced Auditory Serial Addition Test) were performed. RESULTS: Weak correlations between cognitive domains and MRI measures were observed in younger patients (age≤30 years; absolute Spearman's rho = 0.05-0.21), with short disease duration (<2 years; rho = 0.01-0.21), low Expanded Disability Status Scale [EDSS] (≤1.5; rho = 0.08-0.18), low T2 lesion volume (lowest quartile; <0.59 mL; rho = 0.01-0.20), and high brain parenchymal fraction (highest quartile; >86.66; rho = 0.01-0.16). Stronger correlations between cognitive domains and MRI measures were observed in older patients (age>50 years; rho = 0.24-0.50), with longer disease duration (>15 years; rho = 0.26-0.53), higher EDSS (≥5.0; rho = 0.23-0.39), greater T2 lesion volume (highest quartile; >5.33 mL; rho = 0.16-0.32), and lower brain parenchymal fraction (lowest quartile; <83.71; rho = 0.13-0.46). The majority of these observed results were confirmed by significant interactions (P ≤ 0.01) using continuous variables. INTERPRETATION: The association between structural brain damage and functional cognitive impairment is substantially weaker in multiple sclerosis patients with a low disease burden. Therefore, disease stage should be taken into consideration when interpreting associations between structural and cognitive measures in clinical trials, research studies, and clinical practice.